On the accuracy of the formula used to extract trap density in MOSFETs from 1/f noise. (August 2022) - Asanovski, Ruben; Palestri, Pierpaolo; Selmi, Luca
Highlights: The 1/f noise formula used to extract trap densities in MOSFETs is critically re-examined. The formula agrees with NMP models for thick dielectric devices at room temperature. The NBT is underestimated when extracting traps from thin ILs. The NBT extracted from thin-dielectric devices has errors up to 100×. Neglecting gate trapping and the electrostatic scaling factor causes these errors. Abstract: Noise spectroscopy is a powerful non-destructive technique to characterize the quality of gate dielectrics in MOSFETs. Trap densities are routinely extracted by fitting the 1/f part of the drain current noise spectrum with a widely known analytical expression containing several approximations within. This paper compares this 1/f noise analytical expression with microscopic simulations, evaluates its accuracy under different scenarios, and highlights when the main assumptions fall short. It is found that the expression agrees well with non-radiative multi-phonon (NMP) models at room temperature for devices featuring a thick dielectric. However, the formula fails to correctly predict the noise of nowadays aggressively scaled devices, because it neglects trapping/de-trapping with the gate electrode and the electrostatic charge scaling of the traps due to their distance from the channel.